Efficacy and Safety of Topical or Oral Hydrolyzed Collagen in Women with Dermatoporosis: A Randomized, Double-Blind, Factorial Design Study - Guadanhim, Lilia R. S.; Miot, Hélio A. [UNESP]; Soares, Juliana L. M.; Silva, Silas A. M.; Leonardi, Gislaine R.; Lopes, Renato D.; Bagatin, Ediléia (Springer Nature, 2023)
Background: Dermatoporosis defines the progressive chronic cutaneous insufficiency syndrome. Stage I is characterized by cutaneous atrophy, senile purpura, and stellate pseudoscars. Objective: To assess clinical, histologic, quality of life, and biophysical effects of oral and/or topical hydrolyzed collagen (HC) on forearm skin of postmenopausal women with Dermatoporosis stage I. Methods: Double-blind randomized placebo-controlled factorial design study. Two groups of menopausal women with stage I dermatoporosis on forearms were randomized to oral HC 5 g/day or matching placebo, and also to topical serum 2.5% HC or matching placebo once a day, for 6 months. Results: A total of 56 women, age range 60–93 years (mean 69.5 ± 7.3 years) were included. Comparing data from baseline and after 6 months, no significant difference was observed for each intervention nor their comparison, for all efficacy parameters: clinical and quality of life scores, dermal elasticity, thickness and echogenicity, and histologic and immunohistochemical markers (p > 0.1). Limitations: Larger studies to confirm our findings are warranted. Conclusions: In menopausal women with stage I dermatoporosis, oral or topical collagen peptides used alone or in combination do not have benefits on forearm skin after 6 months of intervention, and therefore should not be used routinely in this population. Graphical Abstract: CONSORT flow chart [Figure not available: see fulltext.].
Keywords: Collagen peptides; Cutaneous atrophy; Dermatoporosis; Hydrolyzed collagen; Photoaging; Senile purpura